2012
DOI: 10.1016/j.jep.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Hymenaea stigonocarpa Mart. ex Hayne: A Brazilian medicinal plant with gastric and duodenal anti-ulcer and antidiarrheal effects in experimental rodent models

Abstract: MHs clearly demonstrate antidiarrheal, gastroprotective and cicatrising effects in experimental gastric and duodenal ulcers, and the diet with fruit pulp displays duodenal healing effects. The observed effects may be associated with the antioxidant effect, which may be due the presence of condensed tannins and flavonoids in the bark and fruit of H. stigonocarpa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 60 publications
2
32
0
5
Order By: Relevance
“…The same method carried out to the GGME fractions BTF, BAF, TLF. After oral administration, the acute toxicity and behavioural parameters were described according to the methods of Souza Brito [11]. The observations were performed at 30, 60, 120, 240 and 360 min after the oral treatments.…”
Section: Acute Toxicity Studiesmentioning
confidence: 99%
“…The same method carried out to the GGME fractions BTF, BAF, TLF. After oral administration, the acute toxicity and behavioural parameters were described according to the methods of Souza Brito [11]. The observations were performed at 30, 60, 120, 240 and 360 min after the oral treatments.…”
Section: Acute Toxicity Studiesmentioning
confidence: 99%
“…Furthermore, Snijman et al (2007) report that, besides the potential to alter the cell membrane permeability due to their astringent action, terpenes, mainly diterpenes, acting together with flavonoids, promote antimutagenic effect on cells treated with mutagenic compounds. However, despite Dimech et al (2013) and Orsi et al (2012) reporting the presence of these two chemicals in the alcoholic extract of the the bark of this plant, their mode of action can not yet be infered since their chemical constituents were not fractionated, measured and classified in a specific way. As initially mentioned, few studies have been conducted on the antimutagenic and cytotoxic potential of some species of the genus Hymenaea, however, unlike jatobá-do-cerrado, there already are isolated chemical compounds from these species that promote these activities.…”
Section: Concentrationmentioning
confidence: 98%
“…Thus, under these study conditions, an antimutagenic effect of the concentrations 0.5; 1.0 and 1.5 mg/mL of jatobá-do-cerrado hydroalcoholic extract, versus paracetamol at 0.008 mg/mL, may be suggested. Dimech et al (2013) and Orsi et al (2012), by means of classic and gas chromatography, found that the hydroalcoholic extract of the the bark of H. stigonocarpa Table 2. Number of undifferentiated cells and those in interphase, number of cells under division, and mitotic index values obtained for the A. cepa root cells of the treatment groups Positive Control, Negative Control and Jatoba Control at concentrations of 0.5; 1.0 and 1.5 mg/mL, and Simultaneous Treatment at concentrations of 0.5; 1.0 and 1.5 mg/mL of Hymenaea stigonocarpa alcoholic extract, evaluated at an exposure time of 48 h. consists of flavonoids, especially the isoprenoids; palmitic acid, oleic acid and linoleic acid and diterpenes.…”
Section: Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Após a identificação das plantas coletadas foi realizada uma revisão bibliográfica referente à utilização medicinal de cada uma das espécies. Nessa revisão foram utilizados dicionários de plantas medicinais como Corrêa (1984), levantamentos florísticos de espécies vegetais úteis do Cerrado como Almeida et al (1998) e de plantas medicinais como Brandão (1991), Vieira & Martins (2000), Rodrigues & Carvalho (2001), Rodrigues & Carvalho (2010) …”
Section: Materials E Métodounclassified